Dry sliding and slurry abrasion behaviour of wire arc additive manufacturing – Cold metal transfer (WAAM-CMT) cladded inconel 625 on EN8 steel. (January 2023) - Raushan, Hrishav; Bansal, Anuj; Singh, Vikrant; Singla, Anil Kumar; Singla, Jonny; Omer, Ankita; Singh, Jagtar; Goyal, Deepak Kumar; Khanna, Navneet; Rooprai, Ranbir Singh
Abstract: Inconel 625 was cladded over tillage material EN8 with Wire Arc Additive Manufacturing (WAAM) - Cold metal Transfer (CMT) using varied input parameters. For examining the effectiveness of developed clads; dry sliding and slurry abrasion tests were conducted as per ASTM G65 standards under varying parameters. It has been perceived that cladded specimens have shown higher wear resistance than bare tillage material owing to their comparatively higher microhardness. The superlative results for maximum resistance to mass loss was found at 144 A current, 15.3 V voltage, 5 m/min wire feed speed, and 10 cm/min scanning speed. The bare and Inconel 625 cladded EN8 steel have showed ductile and mixed (ductile as well as brittle) mode of failure, respectively.